2009
DOI: 10.1016/j.drugalcdep.2008.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Changes in feeding and locomotion induced by amphetamine analogs in rats

Abstract: Studies of the biobehavioral actions of psychostimulants commonly focus on locomotion and less commonly on feeding, and only rarely are these measures considered in conjunction within the same animal. The present study compared the impact of (+)-amphetamine and three amphetamine analogs, PAL-287, PAL-313, and PAL-353, on eating and locomotion assessed concurrently using an automated activity/feeding chamber during a daily 45 min session. Each analog is a potent releaser of norepinephrine and of dopamine, but e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 44 publications
(67 reference statements)
4
17
0
Order By: Relevance
“…The present behavioral data are reminiscent of those reported by Wellman et al (2009), who compared locomotor and hypophagic effects of (ϩ)-amphetamine, PAL-353, PAL-313, and the preferential 5-HT releaser 1-naphthyl-2-amino- propane (PAL-287) in male rats. Those investigators found that PAL-353 produced robust hyperactivity similar to (ϩ)-amphetamine, whereas PAL-313 was much less potent and had effects similar to PAL-287 (Rothman et al, 2005).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The present behavioral data are reminiscent of those reported by Wellman et al (2009), who compared locomotor and hypophagic effects of (ϩ)-amphetamine, PAL-353, PAL-313, and the preferential 5-HT releaser 1-naphthyl-2-amino- propane (PAL-287) in male rats. Those investigators found that PAL-353 produced robust hyperactivity similar to (ϩ)-amphetamine, whereas PAL-313 was much less potent and had effects similar to PAL-287 (Rothman et al, 2005).…”
Section: Discussionsupporting
confidence: 70%
“…The selectivity for DA release versus 5-HT release for these drugs ranges from 80-fold DA-selective for m-fluoroamphetamine (PAL-353) to nonselective for p-methylamphetamine (PAL-313) (see Table 1). Various behavioral effects of these analogs in rats and nonhuman primates have been reported (Wee et al, 2005;Negus et al, 2007;Kimmel et al, 2009;Wellman et al, 2009), andKimmel et al (2009) used in vivo microdialysis in squirrel monkey nucleus accumbens to demonstrate that PAL-313 evokes significantly less DA release than PAL-353. It is noteworthy that PAL-313 supports less self-administration behavior in rhesus monkeys compared with other PAL analogs, but the precise role of DA and 5-HT in mediating differences in behavioral responsiveness to these drugs remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Wellman et al compared the psychostimulant effect of three amphetamine analogues, including 4-MA [5]. They concluded that 4-MA had a very low effect on locomotion that is attributed to a high activity at 5-HT transporter.…”
Section: Discussionmentioning
confidence: 99%
“…There are very few published studies on the pharmacology of 4-MA in laboratory animals [4,5]. It has been speculated that, compared to amphetamine, the most pronounced serotonergic action of 4-MA could diminish the psychoactive effects of amphetamine leading to the consumption of repeated and higher doses of contaminated amphetamine [2].…”
Section: Introductionmentioning
confidence: 99%
“…[15,16] Regarding behaviour, in rats and monkeys it has anorectic effects comparable to those of Damphetamine, it increases locomotor activity very little or not at all, and has low positive reinforcement potential. [14,16,17] In humans, in a clinical study implemented in 1950, at doses of 1.5 and 2 mg/kg, anorexia, sweating, nausea and vomiting, elevated blood pressure, hypersialosis, abdominal pain, cough and bronchorrhea were all observed. [18] In its report on the evaluation of risks linked to 4-MA in 2014, the European Monitoring Centre for Drugs and Drug Addiction (EMCDDA) reported 20 cases on non-fatal acute toxicity in 5 European countries, and 21 cases of death backed up by toxicology analyses, having occurred in Belgium, Denmark, Netherlands and UK since 2010.…”
Section: -Mamentioning
confidence: 99%